Enhanced warming of the Northwest Atlantic Ocean under climate change. Issue 1 (8th January 2016) - Saba, Vincent S.; Griffies, Stephen M.; Anderson, Whit G.; Winton, Michael; Alexander, Michael A.; Delworth, Thomas L.; Hare, Jonathan A.; Harrison, Matthew J.; Rosati, Anthony; Vecchi, Gabriel A.; Zhang, Rong
Abstract: The Intergovernmental Panel on Climate Change (IPCC) fifth assessment of projected global and regional ocean temperature change is based on global climate models that have coarse (∼100 km) ocean and atmosphere resolutions. In the Northwest Atlantic, the ensemble of global climate models has a warm bias in sea surface temperature due to a misrepresentation of the Gulf Stream position; thus, existing climate change projections are based on unrealistic regional ocean circulation. Here we compare simulations and an atmospheric CO2 doubling response from four global climate models of varying ocean and atmosphere resolution. We find that the highest resolution climate model (∼10 km ocean, ∼50 km atmosphere) resolves Northwest Atlantic circulation and water mass distribution most accurately. The CO2 doubling response from this model shows that upper‐ocean (0–300 m) temperature in the Northwest Atlantic Shelf warms at a rate nearly twice as fast as the coarser models and nearly three times faster than the global average. This enhanced warming is accompanied by an increase in salinity due to a change in water mass distribution that is related to a retreat of the Labrador Current and a northerly shift of the Gulf Stream. Both observations and the climate model demonstrate a robust relationship between a weakening Atlantic Meridional Overturning Circulation (AMOC) and an increase in the proportion of Warm‐Temperate Slope Water entering the Northwest Atlantic Shelf. Therefore, prior climate change projections for the Northwest Atlantic may be far too conservative. These results point to the need to improve simulations of basin and regional‐scale ocean circulation. Key Points: Northwest Atlantic circulation bias is reduced in a high‐resolution global climate model Atmospheric CO2 doubling over 70–80 years results in an enhanced warming of the Northwest Atlantic The enhanced warming is associated with a weakening AMOC and regional circulation change